SPECIFIC OF USING MASSIVE OPEN EDUCATIONAL ELECTRONIC COURSES IN RUSSIAN AND FOREIGN UNIVERSITIES - Grinshkun, V.V.; Krasnova, G.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
Characteristic feature of informatization of education for several last years is emergence and fast distribution of MOOCs - mass open online courses. Specificity of the Russian education system can’t but affect features of development and deployment of such courses taking into account realities of work of domestic universities. For expansion of opportunities of influence of MOOCs on increase in learning efficiency of students in higher education institutions carrying out the analysis of experience of use of such means of informatization of education, both in Russia, and beyond her limits is expedient. The present article contains transfer and the description of various aspects of emergence and distribution of MOOCs in the world, in general, and in our country, in particular. The short characteristic of possible approaches to development and deployment of MOOCs and their component in domestic system of the higher education is given, examples of the Russian and foreign platforms by means of which such courses become public are given. It is emphasized that universal experience of informatization of the higher education on the basis of use of MOOCs without the corresponding adaptation can’t be applied to training of students in the Russian higher education institutions.